The impact of Chernobyl on health and labour market performance in the Ukraine - Hartmut Lehmann; Jonathan Wadsworth (Institute for the Study of Labor (IZA), 2009)
Using longitudinal data from the Ukraine we examine the extent of any long-lasting effects of radiation exposure from the Chernobyl disaster on the health and labour market performance of the adult workforce. The variation in the local area level of radiation fallout from the Chernobyl accident is considered as a potential instrument to try to establish the causal impact of poor health on labour force participation, hours worked and wages. There appears to be a significant positive association between local area-level radiation dosage and health perception based on self-reported poor health status, though much weaker associations between local area-level dosage and other specific health conditions or labour market performance. Any effects on negative health perceptions appear to be stronger among women and older individuals.
Keywords: H00; J00; 330; Chernobyl; health; labour market performance; Strahlenbelastung; Gesundheit; Wahrnehmung; Erwerbstätigkeit; Arbeitszeit; Ukraine